Melanoma to the Heart. Issue 4 (1st October 2016) - Durham, Charis G.; Hall, James A.; Fidone, Erica J.; Mack, Ryan; Metting, Austin L.
Abstract : Malignant melanoma is the third most common skin cancer yet has the highest mortality rate due to its predilection for metastasis. While the diagnosis of antemortem melanoma with cardiac metastasis is relatively uncommon, diagnosing malignant melanoma itself by first identifying a cardiac metastasis is even more rare. This vignette describes an antemortem diagnosis of melanoma in a 50-year-old woman through identification of metastasis to multiple sites, including the tricuspid valve.